Vaccination burnout impedes the compliance with multiple-dose administration of vaccines - Xueying Fan; Yangguo Zhao; Xinyu Zhang; Shunran Li; Fan Wu; Mingting Cui; Ying Ye; Wangmu Duoji; Shiqiang Jiang; Jianhui Yuan; Caijun Sun (Scientific Reports)
Abstract Timely and complete administration of multiple-dose vaccines is essential to guarantee the efficacy. Our study aimed to investigate how people’s vaccination attitudes changed over the course of the multi-dose vaccination schedule and comprehensively reported a phenomenon of vaccination burnout. The participants’ vaccination burnout levels were quantified by our designed vaccination burnout scale. This study is a retrospective cross-sectional study. Among 3068 valid participants, 2991 had finished the routine two shots of COVID-19 vaccine, and 2367 had a positive attitude towards the primary doses of vaccination. Notably, 232 participants who previously had a positive attitude towards primary doses of vaccination refused to take additional multiple shots, and another 83 had changed their positive attitudes to negative, despite having taken the third shot. Participants whose attitudes or behaviors had changed had higher scores of vaccination burnout than those who still maintained a positive attitude (Z=−8.491, P < .001). The frequency of actively paying attention to the related disease news, occupation, monthly income, and residence of the participants were key factors associated with the vaccination burnout. Interventions should be implemented to alleviate the exhausted attitudes and improve people’s compliance with vaccination schedules against the future pandemic.